Distance learning as a prerequisite for the development of students' creative competencies - Dimitrova, Svitlana; Girya, Nataliya (Technická univerzita v Košiciach, 2021)
Research and experience show that distance learning can be as effective for developing students' creative competencies as traditional face-to-face learning. The development of creative competencies of students requires the creation of a creative environment in the academic space of universities. The use of the electronic course significantly increases the interest of students, provides the teacher with more tools and opportunities to form a creative component, stimulates the student to cognitive and independent work. The variety of forms of work, innovative technologies that can be used in distance learning, provides more opportunities to expand and deepen knowledge, form the necessary skills and qualities like a creativity, that is, creates a concept for the development of new pedagogical technology in the organization of learning.

Дослідження і досвід показують, що дистанційне навчання може бути настільки ж ефективним для розвитку креативних компетентностей студентів, як і традиційне очне навчання. Розвиток креативних компетентностей студентів вимагає створення креативного середовища у навчальному просторі університетів. Застосування електронного курсу значно підвищує зацікавленість студентів, надає викладачу більше інструментів та можливостей для формування креативної складової, стимулює студента до пізнавальної та самостійної роботи. Різноманітність форм роботи, інноваційних технологій що можуть застосовуватися при дистанційному навчанні, надає більше можливостей для розширення та поглиблення знань, формування необхідних навичок та якостей, зокрема, креативності, тобто створює концепцію розвитку нової педагогічної технології в організації навчання.
Keywords: distance learning; creativity; pedagogical technology; дистанційне навчання; креативна складова; педагогічні технології